Effect of heat stress and solar radiation on dry matter intake, biochemical indicators, production, and quality of Holstein and Jersey cows' milk Efeito do estresse calórico e da insolação sobre consumo, indicadores bioquímicos, produção e qualidade do leite de vacas Holandês e Jersey - Hauser A.* (2023)
© 2023, Arquivo Brasileiro de Medicina Veterinaria e Zootecnia. All Rights Reserved.The objective of this work was to compare the dry matter intake, milk yield and quality, physiological and biochemical parameters in Holstein (n=10) and Jersey (n=10) cows under heat stress and insolation, in two treatments: CL – cooling by ventilation and sprinkling and HS – heat stress and insolation. Data were submitted to ANOVA. There was an interaction between treatment and breed and day effect for dry matter intake. For consumption in % of body weight, CL and Jersey cows consumed more. CL cows produced more milk and 3.5% fat-corrected milk. Feed efficiency was similar between treatments and breeds. Fat, lactose, total solids, and somatic cell score did not differ. The concentration of milk urea nitrogen was higher for CL cows. Milk from Holstein cows had greater stability to alcohol, and from HT cows had a greater freezing point of milk. HT cows had higher respiratory rates in the morning and surface temperatures in the afternoon. There were no differences in beta-hydroxybutyrate and glucose concentrations. Heat stress, with insulation, reduces intake, especially in Holstein cows, as well as milk production and increases the freezing point of milk, respiratory rate, and surface temperature.